Epistemic modality in American presidential discourse - Romadlani, M. Masqotul Imam; Harjanto, Tofan Dwi (Politeknik Negeri Bali, 2024)
This research examines the exploitation of epistemic modality markers in political discourse. This research inspects modal auxiliaries and semi-modals use in four speeches addressed by Obama at the annual United Nations General Assembly during his second period as a President of America. Applying both qualitative and quantitative methods, this research is in an attempt to accomplish the whole investigation dealing with explorative and quantification of epistemic modality in Obama’s political discourse. The data were taken from Obama’s speeches from 2013 to 2016 at the United Nations General Assembly. The findings demonstrate that 471 modality markers were found in Obama’s speeches and he frequently delivered epistemic probability with 189 cases or 40.2% modal auxiliaries and semi-modals. Epistemic certainty and possibility were found in 125 cases or 26.6% and in 157 cases or 33.2%. The highest degree of epistemic modality, epistemic certainty, is expressed by employing must, have to, need to, cannot, could not, and may not. Modal should, will, would, be going to, and ought to express epistemic probability and modal can, could, may, might, and be able to are exploited to express the lowest degree of epistemic modality, epistemic possibility. The higher epistemic modality markers involved in a proposition indicate the higher confidence of evaluation and judgment asserted based on the speaker’s knowledge, belief, and evidence. In contrast, the lower epistemic modality markers found indicate lower confidence in the evaluation and judgment of the proposition.